PELATIHAN PEMANFAATAN LIMBAH RUMAH TANGGA DI KELURAHAN SIDODAMAI KOTA SAMARINDA MENJADI PUPUK KOMPOS - Husnul Warnida; Yullia Sukawaty; Rusdiati Helmidanora (Jurnal Abdi Masyarakat Kita, 2021)
Waste is a material that is no longer used so that it is then thrown away. All community activities generate waste, so the volume of waste continues to increase. The community is responsible for processing waste so that it does not have a negative impact on the environment. Waste is one of the factors that play a role in flooding in Samarinda. Household waste in the form of vegetable and fruit peels can be processed into compost. Compost improves soil structure by increasing the organic matter content of the soil and will increase the soil's ability to retain soil water content. The process of making compost is quite easy and can be done independently on a household scale. The training on the use of household waste into compost was addressed to residents of RT.6 RW.2 Jalan Jelawat, Sidodamai, Samarinda Ilir District. This activity aims to provide training on household organic waste management to the people, so that it is not wasted and keeps the environment clean. The expected long-term impacts are the reduction in the volume of municipal waste, reducing the frequency of floods, and improving the community's economy, through the production of compost and agricultural products. The training was held on May 29, 2021 by STIKSAM lecturers and students, and was attended by members of PKK RT.06. The training was conducted using lecture and demonstrated methods. The trainees are interested in making compost and will use compost for ornamental plants and vegetables planted in their yards.